Petrology and geochemistry of high niobium eclogite in the North Qaidam orogen, Western China: Implications for an eclogite facies metamorphosed island arc slice. (15th September 2018) - Chen, Xin; Xu, Rongke; Zheng, Youye; Cai, Pengjie
Graphical abstract: Highlights: Newly-discovered high Nb Paleozoic eclogite is reported in the Lüliangshan terrane. The eclogite underwent multistage metamorphism, constituting a clockwise P–T–t path. Geochemical data reveal that the protolith is high Nb arc basalt. A continental-arc collision model is proposed in North Qaidam. Abstract: To better understand the evolution of the North Qaidam orogen, eclogite that forms lens-like bodies in granitic gneiss was studied in the Lüliangshan terrane, North Qaidam ultrahigh-pressure (UHP) metamorphic belt. Petrographic and mineralogical studies as well as pressure-temperature calculations showed that the eclogite underwent at least three metamorphic stages. Peak eclogite-facies metamorphism at 647–768 °C and ≥3.0 GPa was followed by high-pressure (HP) granulite-facies metamorphism at 815–929 °C/1.61–1.75 GPa and cooling to amphibolite-facies metamorphism at 606–720 °C/0.41–0.56 GPa. Three age groups can be identified via LA-ICP-MS zircon U–Pb eclogite dating: (1) an eclogite-facies metamorphic age of ca. 432–428 Ma, (2) an HP granulite-facies retrograde age of ca. 424–420 Ma, and (3) ages of 415–382 Ma, which constrained the timing of amphibolite-facies metamorphism. The studied eclogite is characterized by high field strength element enrichment, particularly in Nb content (57.8–124 ppm) and flat rare earth element patterns similar to high Nb island arc basalts described in many modern arcs that feature subduction of oceanic slabs. The samples have positive εNd (t) values (+2.1 to +5.1) and positive εHf (t) values (+4.9 to +10.0), indicating that the protolith of the high Nb eclogite was directly derived from the depleted mantle with little crustal contamination. These island arc basalts have been interpreted to have arisen from the partial melting of mantle wedge garnet-amphibole or garnet peridotite metasomatized by slab-dehydrated melts of a subducted oceanic slab. They were emplaced onto the continental block by arc magmatism prior to the main collision event. Then, the island arc materials were dragged into the subduction channel with eclogite-facies metamorphism via subduction of the Qaidam Block.